A Comparative Study on Teaching ESP Writing Using Inductive and Deductive Method in Balikpapan State Polytechnic - Elisabeth Milaningrum (JSHP : Jurnal Sosial Humaniora dan Pendidikan, 2019)
The objectives of this research are to know whether there is any significant difference in students’ writing achievement in Balikpapan State Polytechnic between the students who taught using inductive method and those taught using deductive method and to know which group has higher achievement, the group taught using inductive method or the one taught using deductive method. The research methodology used experimental method. The population of this research is the third semester students of mechanical engineering in Balikpapan State Polytechnic. The sampling technique used cluster random sampling and in collecting the data used a test. In analyzing the data used t-test formula. The result of the research shows that there is a significant difference in the achievement of students’ writing skill between the students taught using inductive method and those taught using deductive method. The mean of the experimental group taught using inductive method is 83 while the mean of the control group taught using deductive method is 70. It shows that the mean score of experimental group is higher than the control group. Therefore, it can be concluded that the students taught using inductive method have higher achievement than those taught using deductive. Key word: comparative, deductive method , inductive method, teaching writing